Darifenacin Hydrobromide loaded nanostructured lipid carrier for oral administration - Ala Allah, Ali kathem; Hussein, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2018)
Darifenacin hydrobromide is a selective ?3 receptor antimuscarinic drug and it is used in the management of urinary frequency, urgency, and incontinence in detrusor instability. It slightly soluble in water, undergoes extensive hepatic first-pass metabolism and has short elimination half-life (3–4 hours). Therefore, It has low bioavailability (15.4 % - 18.6 %). Darifenacin hydrobromide loaded NLCs were formulated by emulsification sonication using different ratios of solid lipid to liquid lipid, different types of surfactants, and different concentration of surfactants. Formula sixteen was considered as an optimized formula based on its particle size, PDI, zeta potential and entrapment efficiency. Formula sixteen subjected to further characterization such as DSC, FT – IR, XRD, AFM, and release study. FT-IR and DSC studies showed no interaction between drug and excipients. XRD study showed that drug in amorphous form. AFM study showed discrete lipid nanoparticles with no aggregation. Release study showed burst release in the first hour followed by sustained and controlled release up to 12 hours. The over all study showed the potential of NLC as a carrier for enhancing the bioavailability of darifenacin hydrobromide as compared to the conventional dosage form. Key words: Darifenacin hydrobromide, nanostructured lipid carrier, bioavailability.